Respon Pelaku Usaha Tentang Kewajiban Sertifikasi Halal (Studi Kasus Kantin Universitas Jambi) - Dela Pauzia; Lucky Enggrani Fitri; Ridhwan Ridhwan (JOURNAL OF SHARIA ECONOMICS, 2024)
This research aims to determine the implementation of the halal certification obligation in the Jambi University canteen, the response of business actors regarding the halal certification obligation in the Jambi University canteen, the inhibiting factors and opportunities for business actors in carrying out halal certification in the Jambi University canteen and strategies for halal certification obligations that can be implemented in the canteen. Jambi University. The research method used is qualitative. The data sources in this research are primary and secondary. The data collection techniques used in this research were interviews and observation. The results of this research show that the implementation of halal certification obligations in the Jambi University canteen can use 2 routes, namely self-declaration and regular. If canteen businesses meet the criteria for self-declaring halal certification, they have the right to carry out self-declaring halal certification at a free service rate. Apart from these criteria, canteen business actors are required to carry out regular halal certification. The response of business actors to halal certification is quite good, although there are still many business actors who do not know how to achieve halal certification. The inhibiting factors for halal certification include lack of knowledge and awareness, lack of access to information and outreach, halal certification procedures which are considered complicated and lack of professional guidance. Then the opportunity factors include the halal certification process which will be assisted by the BPU, the existence of PSKH at Jambi University. The strategy for implementing halal certification obligations in the Jambi University canteen is increasing socialization of government policies regarding halal certification, improving the quality of human resources for institutions and business actors related to halal certification, holding socialization and education activities on halal certification, establishing collaboration with other institutions related to halal certification.